1996
DOI: 10.1056/nejm199610313351803
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of Interleukin-2 Infusions in Patients Infected with the Human Immunodeficiency Virus

Abstract: In patients with HIV infection and base-line CD4 counts above 200 cells per cubic millimeter, intermittent infusions of interleukin-2 produced substantial and sustained increases in CD4 counts with no associated increase in plasma HIV RNA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
205
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(221 citation statements)
references
References 22 publications
13
205
1
Order By: Relevance
“…To our knowledge, no other study has reported such associations between (27). The role of IL-2 in the stimulation of proliferation and differentiation of CD4 and CD8 T lymphocytes is well known, and consistent with these results (28)(29)(30). These findings indicate that khat has indeed the potential to significantly alter the immune response.…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, no other study has reported such associations between (27). The role of IL-2 in the stimulation of proliferation and differentiation of CD4 and CD8 T lymphocytes is well known, and consistent with these results (28)(29)(30). These findings indicate that khat has indeed the potential to significantly alter the immune response.…”
Section: Discussionsupporting
confidence: 80%
“…Thence, innovative approaches aimed at improving immune reconstitution have been proposed as a complement to ART. In particular, cytokines that play an essential role in T cell homeostasis and proliferation, such as IL-2 and IL-7, currently are under clinical investigation (18). In this study, we demonstrated that IL-7 exerts protective effects against the spontaneous apoptosis of both CD4 ϩ and CD8 ϩ T cells derived from HIV-1-infected individuals.…”
Section: Discussionmentioning
confidence: 60%
“…For example, interleukin 2 (IL-2), a cytokine that induces a marked increase in the number of total and naïve CD4 ϩ T cells in HIV-1-infected patients (18), was shown to reduce the levels of T cell apoptosis both in vivo (19) and ex vivo (20); the long-term benefits of this therapeutic regimen are being determined in clinical trials. Another cytokine that is under evaluation as a potential agent of immune reconstitution in HIV-1 infection is IL-7, a key factor in the generation, activation, and homeostasis of the T cell compartment of the immune system (21).…”
mentioning
confidence: 99%
“…In its capacity as a potent immunostimulator, IL-2 has also been explored as an ameliorative treatment for T-cell loss as a consequence of HIV infection (Lotze et al 1984;Kovacs et al 1996). In spite of early promise, a recently reported longterm study suggests no real improvement in disease progression, immune function, or eventual outcome (Abrams et al 2009).…”
Section: Il-2 Agonists: Oncology and Infectious Diseasementioning
confidence: 99%